The relationship between sleep duration and all-cause mortality in the older people: an updated and dose-response meta-analysis - Mengyang He; Xiangling Deng; Yuqing Zhu; Luyao Huan; Wenquan Niu (BMC, 2020)
Abstract Background Short or long sleep duration is proposed as a potential risk factor for all-cause mortality in the older people, yet the results of published studies are not often reproducible. Methods Literature retrieval, study selection and data extraction were completed independently and in duplicate. Only prospective cohort studies were included. Effect-size estimates are expressed as hazard ratio (HR) and 95% confidence interval (CI). Results Summary data from 28 articles, involving a total of 95,259 older people, were meta-analyzed. Overall analyses revealed a remarkably significant association between long sleep duration and all-cause mortality (adjusted HR = 1.24, 95% CI: 1.16-1.33, P < .001), whereas only marginal significance was observed for short sleep duration (adjusted HR = 1.04; 95% CI: 1.00-1.09; P = .033). Funnel plots suggested no publication bias for short sleep duration (P = .392). The probability of publication bias was high for long sleep duration (P = .020), yet the trim-and-fill method strengthened its significance in predicting all-cause mortality. In subgroup analyses, the association of long sleep duration with all-cause mortality was statistically significant in both women (HR = 1.48; 95% CI: 1.18-1.86; P = .001) and men (HR = 1.31; 95% CI: 1.10-1.58; P = .003). By contrast, with regard to short sleep duration, statistical significance was observed in men (HR = 1.13; 95% CI: 1.04-1.24; P = .007), but not in women (HR = 1.00; 95% CI: 0.85-1.18; P = .999) (Two-sample Z test P = .099). Besides gender, geographic region, sleep survey method, baseline age and follow-up interval were identified as possible causes of between-study heterogeneity in subgroup analyses. Further dose-response regression analyses revealed that trend estimation was more obvious for long sleep duration (regression coefficient: 0.13; P < .001) than for short sleep duration (regression coefficient: 0.02; P = .046). Conclusions Our findings indicate a significantly increased risk of all-cause mortality associated with long sleep duration, especially in women, as well as with short sleep duration in men only.